2022
DOI: 10.36348/sjpm.2022.v07i11.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Specificities of Immune Red Cell Antibodies in Adult Patients with Sickle Cell Anaemia and Blood Donors in Uyo, South-South Nigeria: A Case-Control Study

Abstract: Background: Sickle cell anaemia (SCA) is a major public health issue in Sub-Saharan Africa, including Nigeria. Transfusion of red blood cells is an essential therapeutic modality in SCA. Repeated RBC transfusions can cause alloimmunization resulting in haemolytic transfusion reactions, transfusion refractoriness among other complications. Aims and Objectives: The study aimed to determine the prevalence and specificities of immune erythrocyte alloantibodies among adult patients with SCA compared with healthy Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…With regard to ABO and rhesus blood groups, polytransfused subjects of group A+ presented a higher risk of alloimmunization (p=0.004). These results are similar to those found by Akpan et al in 2022 in Nigeria who reported that blood group was significantly associated with alloimmunization (p=0.013) in a study of polytransfused sickle cell patients and blood donors [21].…”
Section: Discussionsupporting
confidence: 92%
“…With regard to ABO and rhesus blood groups, polytransfused subjects of group A+ presented a higher risk of alloimmunization (p=0.004). These results are similar to those found by Akpan et al in 2022 in Nigeria who reported that blood group was significantly associated with alloimmunization (p=0.013) in a study of polytransfused sickle cell patients and blood donors [21].…”
Section: Discussionsupporting
confidence: 92%
“…. This result was comparable to those of Regalado-Artamendi et al [16] in 2021 in Spain, who reports in his series 54.6% of Abs directed against the RH and Kell systems as well as those of Akpan et al [17] in Nigeria in 2022 which reports 66.67% of Ab directed against the Ag of the Rhesus system and 33.3% of Ab directed against the Ag of the Kell and Lutheran (LU) systems combined. This could be explained by the strong immunogenicity of these blood group systems.…”
Section: Allo-immunizationsupporting
confidence: 85%